Determinants of corporate social responsibility disclosure in Indonesian manufacturing companies - Meidawati, Neni; Aulia, Annisa (Journal of Contemporary Accounting, 2020)
Financial report information users needed complete and disclosed information. One of the pieces of information was Corporate Social Responsibility (CSR) activity disclosure. The objective of the research was to find the influence of company size, leverage, profitability, the size of the commissioner board, and shareholdings towards the CSR disclosure. Manufacturing companies’ populations in sectors 1, 2, and 3 were recorded in the Indonesian Stock Exchange. The research sample which used in this research was manufacturing companies in the sector of cement, ceramics, porcelain, and glass, also metal and it is kind with the period year from 2014 until 2018. The research sample was chosen using the purposive sampling method. Hypothetical measurement was analyzed by using the multiple regression method. From the research result, it was proven that profitability had a positive effect on CSR disclosure, and leverage had a negative effect, while variable of company size, the commissioner board size, and shareholdings did not influence the CSR disclosure.